Latency after Preterm Prelabor Rupture of the Membranes: Increased Risk for Periventricular Leukomalacia. (17th July 2014) - Denzler, Annick; Burkhardt, Tilo; Natalucci, Giancarlo; Zimmermann, Roland
Abstract : Objective . To identify the risk factors for cystic periventricular leukomalacia (cPVL) and their implications for deciding between immediate delivery and conservative management of preterm prelabor rupture of the membranes (pPROM). Methods . The following risk factors were compared between cPVL infants and 6440 controls: chorioamnionitis, sex, gestational age (GA), birth weight, pPROM, and pPROM-delivery interval. Factor impact on cPVL risk and clinical decision-making was determined by multivariate logistic regression. Results . Overall cPVL prevalence (n = 32 ) was 0.99/1000 births. All cPVL infants but one were born <34 weeks of gestation and were <2500 g; 56% had histological chorioamnionitis versus 1.1% of controls (OR 35.9; 95%-CI 12.6–102.7). Because chorioamnionitis is a postnatal diagnosis, logistic regression was performed with prenatally available factors: pPROM-delivery interval >48 hours (OR 9.0; 95%-CI 4.1–20.0), male gender (OR 3.2; 95%-CI 1.4–7.3). GA was not a risk factor if birth weight was included. Risk decreased with increasing fetal weight despite a prolonged pPROM-delivery interval. Conclusion . pPROM-delivery interval is the single most important prenatally available risk factor for the development of cPVL. Immediate delivery favors babies with chorioamnionitis but disfavors those with non infectious pPROM. In the absence of clinical chorioamnionitis fetal weight gain may offset the inflammatory risk of cPVL caused by a prolonged pPROM-delivery interval.